THE RELATIONSHIP OF DIALECT WORDS IN THE PRONUNCIATION OF THE KAZAKH AND UZBEK LANGUAGES (IN THE CASE OF NAVOI REGION) - Kulatova Gaziza Djinisbekovna (Scholar Express Journals, 2023)
In this article, the purpose of scientific research in linguistics, the study of specific features of this or that dialect from a deep historical-etymological point of view, in particular, scientific considerations are made about the influence and relationship of the dialect of the Kazakh population living in the Navoi region to the Uzbek language
Keywords: Language; linguistics; dialect; dialectology